An explicit parallel algorithm for solving variational inclusion problem and fixed point problem in Banach spaces - Prasit Cholamjiak (2020)
© 2019, Tusi Mathematical Research Group (TMRG). In this article, we introduce an explicit parallel algorithm for finding a common element of zeros of the sum of two accretive operators and the set of fixed point of a nonexpansive mapping in the framework of Banach spaces. We prove its strong convergence under some mild conditions. Finally, we provide some applications to the main result. The results presented in this paper extend and improve the corresponding results in the literature.